SHRINE SITES KEEPERS IN TRADITIONAL AND MODERN KAZAKHS’ CULTURE: ASSUMPTIONS AND PROBLEM DEFINITION - Shaigozova Zhanerke Nauryzbaevna; Muzafarov Rustam Rakhimovich; Sultanova Madina Ernestovna (Scientific Journal of Pedagogy and Economics, 2019)
Some natural and man-made sites are considered as shrines in Kazakh culture. It became pilgrimage since ancient times and includes mazars (mausoleum graves) of the famous people, who are associated with the cult of aulie. Nowadays observations show that today a keeper is appointed to look after almost each holy site has its known site-keeper. The person who takes care of a mazar is named shyrakshy, while the natural sacred site keeper is named қyzmetshi. Although the institute of sacred place keepers in the Kazakh culture is relatively late historical and cultural phenomenon, which associates with the transition from nomadic to settled lifestyle and Islam dissemination, the study shows a genetic continuity of much earlier forms of ‘people selected by the holy spirit’ in human consciousness. This article aims to review problem definition for this cultural phenomenon and discuss next research steps and prospects.